Wellbeing and welfare states: cross-national comparison of quality of life in market and transition economies - Gopalakrishnan Netuveli; David Blane and Mel Bartley
Cross-national comparisons of quality of life in countries in different stages of transition to a market economy, with old and established economies in Europe and USA will yield valuable lessons. Equally interesting will be to compare these transitional economies to a developing country. In this paper we examine differences in quality of life between the different countries of Western, Eastern and Central Europe, Russia and the USA, and some possible explanations for these variations. We then go on to compare quality of life in the Indian state of Kerala to that in the other nations. Our results show wide disparities in quality of life among these countries with Switzerland, Denmark, Sweden and the Netherlands leading the league table. The lowest levels of quality of life were in Russia, Italy and Greece, followed by the Czech Republic and Poland. Countries with high average quality of life tended to have less inequality in quality of life. Compared to social-democratic welfare regimes, other regime types had reduced quality of life The typology of welfare regime explained 63% of the variation among the countries. When indicators of decommodification and social stratification styles were modelled, 91% of the variation between countries was explained. Kerala had a quality of life better than Italy, Greece, and Russia. There was a definite gradient in quality of life with education. Muslims had lower quality of life and so did tribal people. Both education and operational measures of capability were strongly predictive of quality of life in Kerala. From these findings we conclude that state policies, especially those countering market forces, can explain much of the differences among market and transition economies inequality of life. Similarly fostering human capabilities can also enhance quality of life. However, inequalities in quality of life among sub-populations need to be addressed.